ASUPAN ZAT GIZI MAKRO DAN STATUS GIZI MAHASISWA ASING DI SURABAYA, INDONESIA[Macronutrient Consumption and Nutritional Status of International Students in Surabaya, Indonesia] - Airin Levina; Sri Sumarmi (Universitas Airlangga, 2019)
Nutrient intake is one of the factors affect nutritional status. International students who live in other countries face different environment from their own country. The differences affects food habits, nutritional adequacy level, and nutritional status of international students. This study aimed to analyze the correlation of nutrition intake and nutritional status among international students in Surabaya. This cross-sectional study included 30 respondents. Food consumption was collected by Semi-Quantitative Food Frequency Questionnaire. Nutritional status determined by body weight and height. Chi-square test was used to analyze the correlation variables. The average energy intake of international students were 1,888 ± 379 kcal per day. The percentage of overweight international students were 20% and underweight were 16.7%. The results showed low correlation between energy (r=0.370) and protein (r=0.380) adequacy level with nutritional status, moderate correlation between fat adequacy level (r=0.410) and nutritional status, and no correlation between carbohydrate adequacy level (r=-) with nutritional status. The conclusion was lower macronutrient intake causes inadequacy energy level which causes one third of international students didn’t have normal nutritional status. Therefore, international students need to increase macronutrient intake by increasing meal-portion, choosing balanced food, and not skipping meal time.